2020
DOI: 10.5852/ejt.2020.669
|View full text |Cite
|
Sign up to set email alerts
|

Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex

Abstract: Phlyctinus callosus (Schoenherr, 1826) (Curculionidae, Entiminae, Oosomini) is a species native to the Western Cape province of the Republic of South Africa. It is regarded as a key pest of orchards and vineyards. Detailed observations of its morphology and ecology have shown this species to be a complex of closely related species. In this study we describe the species of this complex, provide morphological and molecular diagnostic tools to distinguish between species, and review their distribution and host pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 1,020 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…not regarded as pests of commercial crops. The species described by Haran et al (2020) as P. callosus sensu stricto is recognised as having spread from South Africa hence literature published from studies in Australia and New Zealand, before the species complex was recognised and elaborated, remains valid for the purposes of this pest categorisation. However, Haran et al (2020) note that it is difficult to morphologically distinguish between female specimens of P. callosus and the newly described species P. xerophilus and that more taxonomic research is needed.…”
Section: Identity and Taxonomymentioning
confidence: 99%
See 3 more Smart Citations
“…not regarded as pests of commercial crops. The species described by Haran et al (2020) as P. callosus sensu stricto is recognised as having spread from South Africa hence literature published from studies in Australia and New Zealand, before the species complex was recognised and elaborated, remains valid for the purposes of this pest categorisation. However, Haran et al (2020) note that it is difficult to morphologically distinguish between female specimens of P. callosus and the newly described species P. xerophilus and that more taxonomic research is needed.…”
Section: Identity and Taxonomymentioning
confidence: 99%
“…nov.). Each of the five new species described by Haran et al (2020) is reported from limited areas within South Africa with four found only in natural or seminatural habitats, i.e. not regarded as pests of commercial crops.…”
Section: Identity and Taxonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological characteristics are often used for species description and identification. Characters such as the deciduous mandibular cusps, corbels on the hind tibiae also occur in Brachycerinae (Curculionoidea: Curculionidae) [ 3 ], and many taxa often include cryptic species complexes [ 5 , 6 ]. The morphological differences between closely related species can be so small that even professional taxonomists struggle with identification [ 4 ].…”
Section: Introductionmentioning
confidence: 99%